Natural convection heat transfer from horizontal concentric and eccentric cylinder systems cooling in the ambient air and determination of inner cylinder location - Atayilmaz, S. Ozgur; Demir, Hakan; Sevindir, Mustafa Kemal; Agra, Ozden; Teke, Ismail; Dalkilic, Ahmet Selim (SPRINGER, 2017)
Heat transfer characteristics of horizontal copper concentric cylinders in the case of natural convection was investigated numerically and experimentally. While the inner cylinder had an electric heater to keep it at a constant temperature, annulus was filled with water. There were two different test sections as bare and concentric cylinder systems located in different ambient temperatures in a conditioned room for the comparison of the results. Comparison of average Nusselt numbers for the air side of the concentric cylinder system and the effective thermal conductivity of the annulus were calculated with both experimental data, numerical results and a well-known correlation. Annulus and the air side isotherms and streamlines are shown for Ra-L = 9 x 10(5)-5 x 10(6) and Ra = 2 x 10(5)-7 x 10(5) respectively. Additionally, a numerical study was conducted by forming eccentric cylinder systems to determine the optimum location of inner cylinder to maximize the heat transfer rate. Comparison of heat transfer rates from bare and concentric horizontal cylinders were done under steady state conditions. Heat transfer enhancement, the effect of the decrease in condensing temperature of the inner cylinder surface on COP of an ideal Carnot refrigeration cycle and rise in COP were determined in the study. Also the optimum location of inner cylinder to maximize the heat transfer rate was determined as at the bottom quadrant of outer cylinder.
Keywords: TURBULENT FREE-CONVECTION; CORRELATING EQUATIONS; CYLINDRICAL ANNULI; ELLIPTIC CYLINDERS; CIRCULAR-CYLINDER; RAYLEIGH NUMBERS; LAMINAR; SIMULATION; SURFACE; WATER; Thermodynamics; Mechanics